Problems of Creating a Favorable Investment Climate in Russian Regions - Pinskaya, Milyausha R.; Melnichuk, Marina V.; Frumina, Svetlana V.; Tikhonova, Anna V. (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to identify the budget- and tax-related problems as may occasionally arise from the interaction of federal and sub-federal authorities hampering the growth of the investment attractiveness of regions, and to develop recommendations on their solution. To this end, a system of indicators and a typological scale have been developed to rank the Russian Federation subjects according to efforts of their regional authorities to build up local tax bases. To provide conditions for “holding” an investor in the territory of a federal subject for a long-term period, it is suggested that the existing subsidy rules be supplemented with tax characteristics. The taxing powers of regions in providing territory-oriented tax incentives are analyzed. The weak points of the powers division that lead to distortion of the local tax competition are identified along with the proposal of measures towards their elimination. Keywords: Budgetary subsidies; tax incentives; favorable investment climate; tax competition. JEL Classifications: H2, O16, R42